Artificial Intelligence-Generated Answers to Patients' Questions on Asthma: The Artificial Intelligence Responses on Asthma Study - Nigro, Mattia; Aliverti, Andrea; Angelucci, Alessandra; Braido, Fulvio; Canonica, Giorgio W; Bossios, Apostolos; Pinnock, Hilary; Boyd, Jeanette; Powell, Pippa; Aliberti, Stefano; Mijakoski, Dragan (Elsevier BV, 2025)
Asthma is a prevalent chronic respiratory disease requiring ongoing patient education and individualized management. The increasing reliance on digital tools, particularly generative artificial intelligence (AI), to answer health-related questions has raised concerns about the accuracy, reliability, and comprehensibility of AI-generated information for people living with asthma.